Improvement of "Premium Coffee" Production in SRIDONORETNO Association of Dampit District, Malang - Riyanto, Sugeng; Muchlisyiyah, Jhauharotul; Arafat, Septrial (Prosiding Seminar; 2019: 2019 International Conference of Interdisciplinary SciencesDO - 10.32503/prosidingseminar.v0i0.7, 2019)
Malang is regency that has a high potential of coffee production which is 7,703 tons every year. Of the several types of coffee producers, one of the well-known is Dampit District which since the Dutch era was known as a coffee producer and until now the Dampit District is still known as the first coffee producer. The coffee quality improvement activity has consistently been started by the SRIDONORETNO Association. Currently the SRIDONORETNO Association's coffee production results are directly absorbed by the community of coffee shops and lovers in Malang (Â± 80 shops in Malang) and several shops outside the city of Malang. Activities undertaken to support consistent quality and increase the production of premium coffee are simply educating the group to raise the number of members participating in the red picking program. Train group members to become quality controllers. Create a processing group by making mobile devices that can serve many groups.